2013
DOI: 10.1088/0957-4484/24/12/125706
|View full text |Cite
|
Sign up to set email alerts
|

Direct investigation of silver photodissolution dynamics and reversibility in arsenic trisulphide thin films by atomic force microscopy

Abstract: The dynamics and reversibility of Ag nanoparticle photodissolution into As2S3 chalcogenide thin films have uniquely been directly measured by continuous AFM imaging during patterned optical illumination. The surface morphology, roughness and particle size distribution have thus been spatially and statistically monitored as a function of time, both during and following optical exposure. Photodissolution was observed to proceed via two mechanisms. In one case, nanoparticles abruptly and nearly completely disappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
3
1
Order By: Relevance
“…t=24 and 30 minutes the AFM images doesn't shown any appreciable change in the Ag density except that an artifact appeared in the right-hand side of the images. At this point, our result is somewhat different from the observation of Palumbo et al [33], where they observed the re-emergence of Ag islands in the post illumination state. In the present case, we did not observe the reappearance of new nanostructures during the period of illumination at longer times, but we could observe some leftover Ag on the surface of the sample.…”
Section: Photo-induced Structural Changescontrasting
confidence: 99%
See 1 more Smart Citation
“…t=24 and 30 minutes the AFM images doesn't shown any appreciable change in the Ag density except that an artifact appeared in the right-hand side of the images. At this point, our result is somewhat different from the observation of Palumbo et al [33], where they observed the re-emergence of Ag islands in the post illumination state. In the present case, we did not observe the reappearance of new nanostructures during the period of illumination at longer times, but we could observe some leftover Ag on the surface of the sample.…”
Section: Photo-induced Structural Changescontrasting
confidence: 99%
“…To analyze the concentrations semi-quantitatively, we have calculated the peak intensity ratio of constituent To get direct evidence of kinetics of Ag photo-dissolution in As2S3 matrix, we performed in-situ real time AFM imaging of the Ag/As2S3/glass heterostructure. Fig.8(a) shows a topographical AFM image of the sample in the as-prepared state, which reveals a uniform nanoparticulate nature of Ag film on the As2S3 matrix, similar to that reported in the literature [33]. nm.…”
Section: Photo-induced Structural Changessupporting
confidence: 81%
“…It is important to note that, apart from PD and PB, photo-diffusion and photodissolution is also quite common in bilayer film of metal and ChG when illuiminated with CW laser [44][45][46][47][48][49]. However, detailed discussion of such effects are beyond the scope of the present study.…”
Section: Photobleaching and Photobleaching In Ternary Ge-as-sementioning
confidence: 87%
“…It is important to note that, apart from PD and PB, photo-diffusion and photodissolution are also quite common in the bilayer film of metal and ChGs when illuminated with CW laser [44][45][46][47][48][49]. However, a detailed discussion of such effects is beyond the scope of the present study.…”
Section: Photodarkening and Photobleaching In Ternary Ge-as-sementioning
confidence: 88%